2020
DOI: 10.1002/art.41473
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Tissue Epigenetic and Gene Expression Analysis Combined With Epigenome Modulation Identifies RWDD2B as a Target of Osteoarthritis Susceptibility

Abstract: Objective. Osteoarthritis (OA) is polygenic, with more than 90 risk loci currently mapped, including at the singlenucleotide polymorphism rs6516886. Previous analysis of OA cartilage DNA identified 6 CpG dinucleotides with methylation levels that correlated with the rs6516886 genotype, forming methylation quantitative trait loci (mQTLs). We undertook this study to investigate these mQTLs and to map expression quantitative trait loci (eQTLs) across joint tissues in order to identify a particular gene as a targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…The effect allele at OA-associated SNPs correlates with an increase in gene expression. The advent of CRISPR-Cas9 and subsequent development of the Cas9 toolbox has revolutionized targeted editing of the genome and epigenome (29). CRISPR-Cas9 deletion of the enhancer confirmed that COLGALT2 was a target gene, while gene expression of RGL1 and TSEN15, which flank COLGALT2, remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect allele at OA-associated SNPs correlates with an increase in gene expression. The advent of CRISPR-Cas9 and subsequent development of the Cas9 toolbox has revolutionized targeted editing of the genome and epigenome (29). CRISPR-Cas9 deletion of the enhancer confirmed that COLGALT2 was a target gene, while gene expression of RGL1 and TSEN15, which flank COLGALT2, remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…For demethylation of the enhancer using dCas9-ten-eleven translocation 1 (TET1), Tc28a2 cells that had been previously stably integrated with a gene expressing an inducible dCas9-TET1 construct were created and cultured as described by Parker et al (29). The 6 sequences targeting the enhancer (Supplementary Table 3, available on the Arthritis & Rheumatology website at http://onlin e libr ary.wiley.com/doi/10.1002/art.41738/ abstract) were ordered from IDT as gRNAs.…”
Section: Methylation Quantificationmentioning
confidence: 99%
“…A T > A SNP at rs6516886, located in a region containing multiple genes, is associated with both KOA and HOA 21 . Parker et al demonstrated that the OA-associated T allele of rs6516886 correlated with increased methylation of neighbouring CpGs 22 . Differential allelic expression was identified for 3 genes in proximity to the SNP, but most notably for the gene RWDD2B, an RWD domainecontaining protein coding gene of unknown function, across multiple joint tissues, with additional evidence of correlation with local CpG methylation.…”
Section: Functional Genetic Analysismentioning
confidence: 99%
“…Rs6516886 was found to be associated with a nearby methylation site (cg20220242, located upstream of RWDD2B ) across several tissues (cartilage, fat pad, synovium and peripheral blood) in osteoarthritis patients ( n = 348). They found that the risk allele ‘T’ of rs6516886 correlates with reduced expression of RWDD2B , which was reversed in a chondrocyte cell model by increasing the methylation levels of RWDD2B methylation [ 46 ].…”
Section: Resolving Genome-wide Association Studies Signalsmentioning
confidence: 99%